City of miracles : a novel - Bennett, Robert Jackson, 1984- (Broadway Books, 2017)
Revenge. It<U+2019>s something Sigrud je Harkvaldsson is very, very good at. Maybe the only thing. So when he learns that his oldest friend and ally, former Prime Minister Shara Komayd, has been assassinated, he knows exactly what to do<U+2014>and that no mortal force can stop him from meting out the suffering Shara<U+2019>s killers deserve. Yet as Sigrud pursues his quarry with his customary terrifying efficiency, he begins to fear that this battle is an unwinnable one. Because discovering the truth behind Shara<U+2019>s death will require him to take up arms in a secret, decades-long war, face down an angry young god, and unravel the last mysteries of Bulikov, the city of miracles itself. And<U+2014>perhaps most daunting of all<U+2014>finally face the truth about his own cursed existence.